Ocena efektywności banków komercyjnych w Polsce za pomocą metody DEA (data envelopment analysis) - Zarzecki, Dariusz; Guzowska, Małgorzata; Wiśniewski, Tomasz; Kisielewska, Magdalena; Byrka-Kita, Katarzyna (Efficiency of the Polish Banking Sector, 2005)
This paper provides a preliminary analysis of the Polish commercial banking sector in 2001 using Data Envelopment Analysis (DEA). DEA is employed to examine the cost structure, profitability and thus the efficiency of the commercial banks. The results have implications for the future of the industry as it adapts to the new competitive pressures which will inevitably result from Poland's membership of an enlarged Single European Banking sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 463-479